Value in tourist experiences: How nature-based experiential styles influence value in climbing. (December 2019) - Vespestad, May Kristin; Lindberg, Frank; Mossberg, Lena
Nature-based adventure experiences constitute a significant segment of the tourism industry and understanding consumers' conceptualisations of value is crucial. The aim of this study is to understand how the perceived value of the climbing experience differs within the climbing community. Interviews with climbers revealed that multiple aspects of the climbing experience are valued, including efficiency, play, excellence, aesthetics, status, emotion, esteem and authenticity. The results highlight that conceptualisations of value vary with experiential style. The study thus adds to the conversation on what creates value in the climbing experience and how this fluctuates throughout the climbing experience. The study contributes to our understanding of nature-based experiences and to the development and marketing of adventure experiences. The results imply that building a strong climbing image at destinations and being involved in the climbing community represent key issues that contribute to co-creating value in the tourist experience.